2018
DOI: 10.1177/1849454418782617
|View full text |Cite
|
Sign up to set email alerts
|

Improved ovarian cancer EMT-CTC isolation by immunomagnetic targeting of epithelial EpCAM and mesenchymal N-cadherin

Abstract: Epithelial cell adhesion molecule (EpCAM)-targeted capture remains the most common isolation strategy for circulating tumor cells (CTCs). However, epithelial-to-mesenchymal transition (EMT) leads to decreased epithelial EpCAM expression affecting the optimal CTC capture. In this study, we tested a cohort of ovarian cancer cell lines using flow cytometry to identify N-cadherin as the additional immunomagnetic cell surface target for ovarian cancer cell isolation. Combined immunomagnetic targeting of mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 30 publications
1
56
0
1
Order By: Relevance
“…The negative selection used for CTC culture (CD45 depletion), rather than the positive selection used for CTC enumeration (EpCAM capture) was critical to detect these cells. The optimal isolation method of CTCs continues to evolve in the face of these issues, and while more emphasis has been given to epithelial to mesenchymal transition (EMT) phenotype CTCs in recent years 41 , the data presented here highlight the persistent challenges identifying the optimal markers to isolate CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…The negative selection used for CTC culture (CD45 depletion), rather than the positive selection used for CTC enumeration (EpCAM capture) was critical to detect these cells. The optimal isolation method of CTCs continues to evolve in the face of these issues, and while more emphasis has been given to epithelial to mesenchymal transition (EMT) phenotype CTCs in recent years 41 , the data presented here highlight the persistent challenges identifying the optimal markers to isolate CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of phenotypic heterogeneity among CTCs has been reported (57,67), and while most current CTC detection methods only target EpCAM and/or CK to enrich epithelial CTCs, they may fail to recognize other CTC phenotypes that lack expression of these markers. Since the present study was conducted, increased isolation yields have been shown using an antibody against the mesenchymal marker N-cadherin (68), and using an enrichment strategy combining different antibodies specific for surface proteins and extracellular matrix (69). Unfortunately, no commercially available isolation method combining epithelial and mesenchymal markers was available at the time of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…For PCa, increased CTC counts are associated with earlier disease progression and shorter OS, with enumeration of PCa CTCs using the CellSearch CTC platform gaining FDA approval as a prognostic indicator [175]. While common CTC isolation and analysis techniques favour epithelial CTCs, there have been numerous advances in improving capture, detection, and analysis of EMT-CTCs by screening for epithelial and mesenchymal marker expression [176][177][178][179][180][181]. Equally, as Table 1 shows, several major signaling pathways implicated in EMT have, to some extent, been analysed in CTC samples.…”
Section: Analysis Of Pca Ctcs To Explore the Ar-akt-yap Connection Anmentioning
confidence: 99%
“…Protein detection is usually limited to immunocytostaining which relies on antibody-based detection and the number of microscope channels available with 3 usually dedicated to detection of a CTC marker (often cytokeratin), a nuclear marker such as DAPI, and exclusion of a blood cell marker usually CD45. Nevertheless, some studies have detected additional proteins such as EMT markers [21,22,176] or posttranslational modifications such as phosphorylation of pFAK, pPI3K, pSRC, pEGFR, and pAkt [53,[201][202][203][204]].…”
Section: Analysis Of Pca Ctcs To Explore the Ar-akt-yap Connection Anmentioning
confidence: 99%